2010
DOI: 10.1540/jsmr.46.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Z-338, a novel gastroprokinetic agent, on the actions of excitatory and inhibitory neurotransmitters on neurons in area postrema

Abstract: We investigated the effects of the novel gastroprokinetic agent Z-338 on the actions of excitatory and inhibitory neurotransmitters on neurons in area postrema (AP). Iontophoretic applications of acetylcholine (ACh), AMPA and NMDA increased, while GABA suppressed the firing rates of AP neurons recorded by extracellular electrodes. Z-338 (10 µM) suppressed the ACh-induced acceleratory and GABA-induced inhibitory actions without affecting the excitatory actions of AMPA and NMDA. Under voltageclamp conditions, ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Several recent studies suggested that the pharmacological potency of acotiamide was based on inhibition of acetylcholinesterase (AChE), regulation of muscarinic autoreceptors and regulation of gene expression of γ‐aminobutyric acid (GABA) transporters in the medulla oblongata . Akaike et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies suggested that the pharmacological potency of acotiamide was based on inhibition of acetylcholinesterase (AChE), regulation of muscarinic autoreceptors and regulation of gene expression of γ‐aminobutyric acid (GABA) transporters in the medulla oblongata . Akaike et al .…”
Section: Introductionmentioning
confidence: 99%
“…Akaike et al . reported that the excitatory or inhibitory effects of acotiamide on the firing rates of neurons or actions of nicotine and GABA on area postrema (AP) neurons may explain postmeal relaxation in rats. Seto et al .…”
Section: Introductionmentioning
confidence: 99%
“…It also decreased the inhibitory action of GABA; however, this latter effect required relatively high concentrations of acotiamide in the slice preparations (3 vs 30 µM). The authors concluded that acotiamide modifies the firing of neurons of the AP largely by its antagonism of nicotinic receptors and, to some extent, GABA A receptors [25].…”
Section: Drug Profilementioning
confidence: 99%
“…Increased cholinergic input from cholinergic interneurons to inhibitory motor neurons in the proximal stomach has the potential to induce such effects [3]. Alternatively, the effects of acotiamide on the AP neurons may also contribute to enhanced accommodation [25].…”
Section: Drug Profilementioning
confidence: 99%
See 1 more Smart Citation